Intercultural Business Communication - Fathia Sefiyola; Amalia Nur Halisa; Ayla Azzahra; Sri Dia Sari; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
This article examines the role of intercultural business communication in the context of international collaboration, focusing on two main dimensions. First, the study analyzes how identity negotiation processes and positioning theory influence the construction of shared meaning among individuals from different cultural backgrounds. Second, the article explores the dynamics between structure-oriented and process-oriented approaches in mitigating the risks of communication failure and enhancing the effectiveness of cross-cultural business interactions. The method employed is a non-systematic systematic article review with thematic synthesis of selected literature. The findings indicate that identity negotiation occurs dynamically through discursive practices and participation in communities of practice, while the integration of structural and processual approaches is shown to be critical in establishing common ground and reducing stereotypes. The implications of this study highlight the importance of communicative flexibility, mutual recognition, and languaging competence in fostering inclusive and effective interactions within complex global business environments.